2016
DOI: 10.1104/pp.16.00234
|View full text |Cite
|
Sign up to set email alerts
|

The Chloroplastic Protein THF1 Interacts with the Coiled-Coil Domain of the Disease Resistance Protein N′ and Regulates Light-Dependent Cell Death

Abstract: One branch of plant immunity is mediated through nucleotide-binding/Leu-rich repeat (NB-LRR) family proteins that recognize specific effectors encoded by pathogens. Members of the I2-like family constitute a well-conserved subgroup of NB-LRRs from Solanaceae possessing a coiled-coil (CC) domain at their N termini. We show here that the CC domains of several I2-like proteins are able to induce a hypersensitive response (HR), a form of programmed cell death associated with disease resistance. Using yeast two-hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 92 publications
1
44
0
1
Order By: Relevance
“…According to the model, Thf1 inhibition will lead to disturbed sugar sensing and/or plastid functionality, which have to be postulated as requirements to support obligate biotrophic pathogens such as powdery mildew fungi. The possibility of Thf1 as inhibitor of resistance components such as R-proteins (Hamel et al , 2016) is also included in the model and would be compatible with the observed, rapid HvARM1 TIGS effect on haustorium formation. The role of Thf1 in necrotrophic interactions may be opposite, i.e.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…According to the model, Thf1 inhibition will lead to disturbed sugar sensing and/or plastid functionality, which have to be postulated as requirements to support obligate biotrophic pathogens such as powdery mildew fungi. The possibility of Thf1 as inhibitor of resistance components such as R-proteins (Hamel et al , 2016) is also included in the model and would be compatible with the observed, rapid HvARM1 TIGS effect on haustorium formation. The role of Thf1 in necrotrophic interactions may be opposite, i.e.…”
Section: Discussionmentioning
confidence: 82%
“…Toxin A-treatment also triggered an oxidative burst in leaves of wheat and barley (Manning et al , 2010, Manning et al , 2007, Pandelova et al , 2012) thereby providing a link of Thf1 function with ROS control, at least in chloroplasts, and propose a mode of action of Toxin A. Additional support for a relevant role of Thf1 in plant susceptibilty is provided by results showing interaction of the Thf1 protein with the I2-like coiled-coil (CC) domains of several NB LRR-type resistance proteins (Hamel et al , 2016). One of the well-examined members of this group is the N protein mediating resistance in Nicotiana tabaccum against most Tobamoviruses.…”
Section: Discussionmentioning
confidence: 94%
“…S4). Studies have reported that light-dependent ROS production in chloroplast leads to the HR-like cell death and antiviral resistance (Chandra-Shekara et al ., 2006; Liu et al ., 2007; Chen et al ., 2015; Hamel et al ., 2016). However, the significance of SA in cell death in the present model system needs to be studied further.…”
Section: Discussionmentioning
confidence: 99%
“…Sensor NLRs in pairs have an additional integrated domain 29 that is unusual and functions in recognizing effector proteins; this domain then relieves the 30 regulation of the executor NLR, resulting in activation of immune responses. The typical 31 NLR pairs are RESISTANCE TO RALSTONIA SOLANACEARUM 1 (RRS1)/RESISTANCE 32 TO PSEUDOMONAS SYRINGAE 4 (RPS4) in Arabidopsis thaliana and RESISTANCE 33 GENE ANALOG 5 (RGA5)/RGA4 in rice (Oryza sativa). These genes are genetically linked 34 and oriented head-to-head so that they may share a promoter for simultaneous regulation of 35 transcription.…”
Section: Introductionmentioning
confidence: 99%
“…However, G10-381 NLRs are not the only group that contains autoactive CC domains. It was reported that 382 transient overexpression with the tomato or tobacco CC domain of the I2-like NLR induces 383 cell death in N. benthamiana, but this does not occur with the CC domain of pepper I2-like 384 NLRs(31). Interestingly, C-terminal tagging of the CC domain of pepper I2-like NLR with…”
mentioning
confidence: 99%